STRATEGI KESANTUNAN BERBAHASA DALAM TALK SHOW Q&A DAN RELEVANSINYA TERHADAP PEMBELAJARAN BAHASA INDONESIA TINGKAT SMP - Rika Amalia; Sri Budi Astuti (Buana Bastra, 2020)
The purpose of this study to describe the politeness strategies of Brown and Levinson in the Q&A talk show and describe the relevance of politeness-language strategies towards learning Indonesian at the Middle School level. The theory used to solve the problem in this study is the theory of Brown and Levinson. While the approach used is descriptive qualitative approach with data collection techniques namely documentation techniques. The results of this study indicate that the forms of Brown and Levinson's politeness strategy that occurred in the Q & A talk show in August 2018 consisted of Brown and Levinson's first politeness strategy, namely without strategies found that included speech without strategy. The second strategy of brown politeness and Levinson's positive politeness strategy is found to pay attention to the opponent's speech, exaggerate attention, agreement, and sympathy, intensify the opponent's attention by dramatizing facts, intensify using group identity markers, request approval with general topics or repeat part or all, avoiding disagreement by pretending to agree, using jokes, expressing understanding of the wishes of speakers, giving offers or promises, showing optimism, involving speakers in activities, giving questions asking for approval, giving gifts. Where negative politeness strategies are found to be pessimistic, minimize coercion, and apologize. Finally, the Off Record strategy was found which was included in the strategy. The relevance of the results of the study can be applied in learning Indonesian in junior high school class IX 3.9-4.10.